Effect of catalysts on the yield and properties of lignin form microwavedassisted acetosolve extraction of oil palm empty fruit bunch fibres. - Muhammad Nor, Arifin; Rasidi, Roslan; Nurjannah, Salim; Siti Noor Hidayah, Mustapha; Sarani, Zakaria; Chin-Hua, Chia; Mohd Shaiful, Sajab (Malaysian Palm Oil Board, 2021)
cetosolv is an enhancement organosolv technique utilising acetic acid as solvent and produces high purity of lignin. However, the limitation of this technique in the conventional heating method is the high energy consumption during a long reaction time. Therefore, the employment of microwave is used to overcome this limitation with the expectation of a lower power consumption and short reaction time. In this study, three types of catalysts, sulphuric acid (H2SO4), aluminium choride (AlCl3), and chromium nitrate [Cr(NO3)3] were used to investigate the lignin extraction performance and its properties from microwave-assisted acetosolv (MWA) treatment of oil palm empty fruit bunches (EFB). The highest yields of lignin (76.98%) were obtained using an aqueous solution of acetic acid combined with 3.0% of H2SO4 under 110°C for 30 min. Meanwhile, AlCl3 performed almost similar to H2SO4, providing lignin yield of 71.57% at the highest temperature of 110°C. The usage of microwave-assisted technique also produces a high yield and high purity of lignin. It is also proven that AlCl3 can be a substitute to Bronsted acid for lignin extraction. However, Cr(NO3)3 was found not suitable for the lignin’s extraction despite having a high potential for cellulose extraction.